Clusters formation and fragmentation of nitromethane at 266 nm - D. Martínez; A. Guerrero; E. Prieto; I. Álvarez; C. Cisneros (MethodsX, 2020)
We carry out experiments on the fragmentation of nitromethane by multiphoton absorption at the wavelength 266 nm. This was conducted in a reflectron (Jordan), modified in the laboratory. Due to the large number of fragments, special care has been taken into the calibration of the system, in the simultaneity between the laser pulse and the sample, and the associated electronics to ensure that produced fragment spectra arise from the interaction laser-sample. We emphasize the next aspects of the method: • Simple design for introducing a gas sample at laser interaction region to facilitate the cluster formation • Astonishing number of fragments produced by multiphoton absorption.